أثـــر الحــذف فـــي الانسجــــام الـنــصّــــــــيّ دعاء عرفة للإمام الحسين ( ) أنموذجاً - يوسف فيصل العيدانيّ جلال الدين; عويد الركابي أحمد نادي (Journal of College of Education, 2019)
Modren text lesson is still evolvable and add. Itˈs attributies, element’s and it’s applications didn’t take it’s final from and didn’t reach maturity dgree . perhaps the reason for this is distinguish each language from the other with properties and clear signs . Deletion element that Halide and Ruqyah Hassan consider it one of the five elements of cohesion is actors in modern text lesson . Delete a vocabulary or phrase from the text stimulates the reader to find the text link between the text vocabularies and its sentences . thus the consistency and coherence of the text is show This search is an attempt to show deletion effect in the litrary religious text coherence . It’s (Duˈaa Emam Hussein in Arafaˈs day) . Search started with definition of deletion language and convention . Then deletion at the ancient and modernists . The search had parts of deletion(according to subdivisions of Halide and Ruqyah Hassan)After that applied models were taken from the Duˈaa that show deletion effect in text coherence and a chieving graphical touches from the core of Arabic rhetoric , especially that the Duˈaa is Emam Hussein . He is from era of eloquence and rhetoric and his speech should have been taken out in grammar martyrdom for correct grammar base . We don’t forget he is heir the eloquence and rhetoric from grandfather , father and mother .